Pilgrimage Tourism to Wali Tombs and Halal Destination Management Based on Sharia Values: Wisata Ziarah Wali dan Pengelolaan Destinasi Halal Berbasis Religius - Kusumaningtyas, Menur; Ulfah, Indar Fauziah; Latifah, Fitri Nur; Putranto, Johni Harius (Perisai : Islamic Banking and Finance Journal, 2024)
This study explores the relationship between pilgrimage tourism to Wali tombs and halal tourism, focusing on the integration of Sharia values in the management of religious destinations. In the context of East Java, this research examines the application of Sharia principles by site managers to maintain the sanctity and integrity of the sites, as well as its impact on the experience of Muslim tourists. The study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with site managers, tourists, and local communities, along with direct field observations. The findings show that the application of Sharia management in site operations not only enhances tourist satisfaction but also strengthens the local economy and cultural preservation. However, the study also found a lack of understanding of Sharia values among some site managers. This research provides recommendations for site managers to create tourist destinations aligned with Sharia principles, supporting the growth of halal tourism in Indonesia. It is hoped that the results of this study can serve as a reference for developing policies on sustainable and responsible religious tourism.This study has several limitations, including the geographical scope limited to East Java and restricted access to all pilgrimage site managers. Therefore, the findings cannot be generalized to all religious tourism destinations in Indonesia. Further research covering a broader area is recommended to enrich the findings.